Modelling the impacts of climate change on water supply and demand balance of Büyük Menderes basın - Erkol, Zülküf İbrahim. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2020., 2020)
With impacts of climate change and increasing agricultural water requirement rates due to irrigated land area expansion, freshwater demand in Büyük Menderes Basin (BMB), Turkey increases. Besides, usage of low-efficiency irrigation systems exacerbates the water demand and supply balance in BMB. Hence, enhanced water management practices are crucial to achieve sustainable freshwater management in BMB under climate change. In this study, Water Evaluation and Planning Systems (WEAP) modeling program, as an Integrated Water Resources Management (IWRM) tool, is utilized to model the effects of climate change and agricultural changes (i.e., irrigation system changes, irrigated land expansion) on water demand and supply balance by 2100. The model has different agricultural management and climate change scenarios. The climate change scenarios are based on the outputs of CNRM-CM5.1 and MPI-ESM-MR global circulation models (GCMs), agricultural management scenarios investigate the impacts of changes in irrigation systems and irrigated land area. According to CNRM-CM5.1, unmet agricultural water demand increases under all simulated scenarios in BMB between 2019 and 2100. However, according to results of MPI ESM-MR, total unmet agricultural water demand is significantly lower compared to that of CNRM CM5.1. Regional differences of climate change impacts on reservoir storage volumes are also critical. Under CNRM-CM5.1 results, reservoirs in Aydın show declining storage volume rates compared to their average baseline rates and reservoirs in Denizli indicate increasing storage volume rates. Under MPI-ESM-MR results, average storage volume rates increase in reservoirs located in Aydın and Denizli. This study demonstrates the role of GCMs and their inherent uncertainties in coupled modeling systems for freshwater ecosystems.
Keywords: Climate change.; Büyük Menderes River Valley (Turkey).; Water supply -- Turkey.